2023
DOI: 10.3390/foods12122394
|View full text |Cite
|
Sign up to set email alerts
|

Paraprobiotics and Postbiotics—Current State of Scientific Research and Future Trends toward the Development of Functional Foods

Abstract: The potential of paraprobiotics and postbiotics to be used as beneficial agents for human health has caused an effort by the scientific community to gather information about the bioactivity of these compounds and production methods. Understanding the evolution of scientific research in this area of study is important to understand the future perspectives and the main bottlenecks of scientific and technological development involving these compounds. In this scenario, this review work used a bibliometric analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The categorization depends on demands from different regulatory authorities on probiotic manufacturers and indications of use [3]. In recent years, several beneficial probiotics have been isolated from the environment and from fermented foods [4]. Microbial fermentation is a well-established and widely adopted technology to preserve foods and increase their shelf-life, also preventing human illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…The categorization depends on demands from different regulatory authorities on probiotic manufacturers and indications of use [3]. In recent years, several beneficial probiotics have been isolated from the environment and from fermented foods [4]. Microbial fermentation is a well-established and widely adopted technology to preserve foods and increase their shelf-life, also preventing human illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a great field of interest regarding the use of microbiotics and nutribiotics in foods, both for animal nutrition and for humans in terms of functional foods [32], and also in the pharmaceutical industry [22,33].…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, it has been reported that more beneficial probiotics have been isolated from the environment and fermented foods. Probiotics need to reach the intestines alive, while a new group, termed paraprobiotics, defined as inactivated (non-viable) microbial cells with a beneficial effect on the human body even in killed bacteria, has been proposed [5].…”
Section: Introductionmentioning
confidence: 99%